Dosimetric characterization of CdZnTe radiation detectors under electron-beam irradiation - Chansun Park; Jiwon Seo; Sangsu Kim; Hyojung Kim; Jung-Yeol Yeom; Shinhaeng Cho (PLoS ONE, 2026)
With the growing complexity of modern radiotherapy, the demand for dosimeters capable of delivering real-time, high-resolution, and reliable measurements has grown significantly. Although cadmium–zinc–tellurite (CZT) detectors have emerged as potential solutions to this growing demand, the lack of comprehensive characterization data for these detectors deters their application in clinical electron-beam dosimetry, especially for high-precision tasks such as small-field and point-dose dosimetry. In this study, we systematically characterized CZT detectors, emphasizing the performance trade-offs associated with detector thickness for therapeutic electron-beam dosimetry. The performance of two CZT detectors (6 × 6 mm²), with thicknesses of 5 and 8 mm, was evaluated using a clinical linear accelerator (LINAC) over an electron energy range of 6–18 MeV. Both detectors demonstrated stable baseline performance, including proportional dose linearity (R² > 0.997), dose-rate independence, and excellent long-term stability (<1.3% variation over two months). Furthermore, a distinct thickness-dependent trade-off was identified: while both configurations exhibited highly comparable dose responses at the 6-MeV baseline, the 8-mm detector exhibited better energy capture efficiency for higher-energy electrons. By contrast, the 5‑mm detector offered enhanced angular isotropy with respect to the gantry angle as well as reduced signal variation (±3.5% vs. ± 6.4%), emerging as more suitable for rotational therapies and geometrically demanding scenarios. Additionally, a nonmonotonic energy dependence was observed, characterized by a pronounced response peak at 15 MeV, which was likely attributable to bremsstrahlung photon contamination from the LINAC head. These findings demonstrate that detector thickness serves as an application-specific optimization factor for sensitivity and angular fidelity, offering a practical framework for deploying CZT detectors in both initial clinical evaluations and challenging extra-clinical radiation environments.